Pengaruh Pendidikan Keluarga dan Media Massa pada Sikap Mahasiswa terhadap Pendidikan Seksualitas - B. Sukarno (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
The purpose of the study was to find out the effect of family education and mass media on students’ attitudes toward sex education. Using correlational design, the study involved 93 third-semester students of Education Faculty of Sebelas Maret University, who were selected out of 125 students using multistage random sampling technique. The data, which were collected through questionnaire, were analyzed using Pearson's product moment correlation, t-test, and multiple regression. The results indicate that family education and mass media had a significant effect on students’ attitudes toward sex education.